Plain Language (the right to understand the Law) - Arenas Arias, Germán Jair (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: For some years, the use of plain language has been promoted in legal and formal documents for strengthen access to public information, trust in institutions, social control mechanisms and legal security. Different international associations and national plain language networks have committed themselves to what they call the right to understand the law and justice. This article reviews the conceptual construction of plain language, its origins in the theory of modern legislation, its impact in contemporary democracies and in the communication between State and citizens.
Keywords: legal language; clarity; trust; communication; trsnaparency; public information